2011
DOI: 10.1117/1.3638134
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oximeter for the blue-green oximetry technique

Abstract: Abstract. Retinal oximetry offers potential for noninvasive assessment of central venous oxyhemoglobin saturation (SO 2 ) via the retinal vessels but requires a calibrated accuracy of ± 3% saturation in order to be clinically useful. Prior oximeter designs have been hampered by poor saturation calibration accuracy. We demonstrate that the bluegreen oximetry (BGO) technique can provide accuracy within ± 3% in swine when multiply scattered light from blood within a retinal vessel is isolated. A noninvasive on-ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Crittin et al used similar optical approach in developing their two-wavelength oximetry system, 9 while Hammer et al developed an oximetry instrument that also captured two fundus images simultaneously with two wavelengths of light, but with a different optical approach. 10 Other groups using diverse approaches also have contributed to the field of retinal oximetry, such as Denninghoff et al, who developed a multiwavelength oximetry system, 11,12 Ramella-Roman et al who introduced a multiaperture camera system for retinal oxygen saturation measurement, 13 Kagemann et al who used Fourier domain optical coherence tomography to assess spectral oximetry, 14 Li et al who used an adaptive optics confocal scanning laser ophthalmoscope to measure oxygen saturation in small retinal vessels, 15 Khoobehi et al who developed a hyperspectral system that has been used mainly for oxygen saturation measurements of optic nerve heads in monkeys, 16,17 Harvey et al who developed a hyperspectral instrument for measuring retinal oxygen saturation in vivo and in a model eye, [18][19][20] and Humayun's group who developed different hyperspectral system for measuring oxygen saturation within retinal vessels. 21,22 For review see the report of Harris et al 23 Modern spectrophotometric retinal oximetry takes advantage of the great development of digital cameras and computer technology that has taken place in the last few decades.…”
Section: Discussionmentioning
confidence: 99%
“…Crittin et al used similar optical approach in developing their two-wavelength oximetry system, 9 while Hammer et al developed an oximetry instrument that also captured two fundus images simultaneously with two wavelengths of light, but with a different optical approach. 10 Other groups using diverse approaches also have contributed to the field of retinal oximetry, such as Denninghoff et al, who developed a multiwavelength oximetry system, 11,12 Ramella-Roman et al who introduced a multiaperture camera system for retinal oxygen saturation measurement, 13 Kagemann et al who used Fourier domain optical coherence tomography to assess spectral oximetry, 14 Li et al who used an adaptive optics confocal scanning laser ophthalmoscope to measure oxygen saturation in small retinal vessels, 15 Khoobehi et al who developed a hyperspectral system that has been used mainly for oxygen saturation measurements of optic nerve heads in monkeys, 16,17 Harvey et al who developed a hyperspectral instrument for measuring retinal oxygen saturation in vivo and in a model eye, [18][19][20] and Humayun's group who developed different hyperspectral system for measuring oxygen saturation within retinal vessels. 21,22 For review see the report of Harris et al 23 Modern spectrophotometric retinal oximetry takes advantage of the great development of digital cameras and computer technology that has taken place in the last few decades.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts to develop and improve retinal oximetry, many limitations still exist. 7 The accuracy of retinal oximetry is affected by factors such as variations in vessel size 15 and pigmentation, 6 multiple light paths 16,17 and vessel wall thickness, 7 and others. Variations in vessel size and pigmentation are considered to have a major impact on the accuracy of sO 2 measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen saturation was found to be 101% to 102% and 65% in the retinal arteries and veins, respectively, suggesting that the EOX is sensitive to retinal oxygen saturation. In 2011, Denninghoff et al 14 reported on the use of a new modified confocal SLO (ROx-3) for blue-green oximetry in both swine and human subjects. Results on retinal oxygen saturation were in the same range as reported by other research groups.…”
mentioning
confidence: 99%